In and out of School Literacy Practices - Yakelin Salinas Vacca (Asociación Colombiana de Profesores de Ingles, 2009)
In this article I describe and discuss some studies that have been conducted in the field of literacy in and out of school in the Latin American context as well as in some other regions. I also relate those studies and some theories about literacy practices to my own experience as a teacher. Here I cite the findings of an exploratory study with a group of students from the Extension Courses at a public university in Bogotá on some literacy practices in and out of the school context. This experience disclosed interesting aspects in regard to the way students construct knowledge, not only by resorting to their previous knowledge but also by constructing and conveying their own meaning. In addition, I give an account of in and out of school literacy practices in the context of globalization and the use of new technologies of information and communication.